Assessing refugee healthcare needs in Europe and implementing educational interventions in primary care: a focus on methods - Christos Lionis; Elena Petelos; Enkeleint-Aggelos Mechili; Dimitra Sifaki-Pistolla; Vasiliki-Eirini Chatzea; Agapi Angelaki; Imre Rurik; Danica Rotar Pavlic; Christopher Dowrick; Michel Dückers; Dean Ajdukovic; Helena Bakic; et al. (BMC, 2018)
Abstract The current political crisis, conflicts and riots in many Middle Eastern and African countries have led to massive migration waves towards Europe. European countries, receiving these migratory waves as first port of entry (POE) over the past few years, were confronted with several challenges as a result of the sheer volume of newly arriving refugees. This humanitarian refugee crisis represents the biggest displacement crisis of a generation. Although the refugee crisis created significant challenges for all national healthcare systems across Europe, limited attention has been given to the role of primary health care (PHC) to facilitate an integrated delivery of care by enhancing care provision to refugees upon arrival, on transit or even for longer periods. Evidence-based interventions, encompassing elements of patient-centredness, shared decision-making and compassionate care, could contribute to the assessment of refugee healthcare needs and to the development and the implementation of training programmes for rapid capacity-building for the needs of these vulnerable groups and in the context of integrated PHC care. This article reports on methods used for enhancing PHC for refugees through rapid capacity-building actions in the context of a structured European project under the auspices of the European Commission and funded under the 3rd Health Programme by the Consumers, Health, Agriculture and Food Executive Agency (CHAFEA). The methods include the assessment of the health needs of all the people reaching Europe during the study period, and the identification, development, and testing of educational tools. The developed tools were evaluated following implementation in selected European primary care settings.